Upaya Peningkatan Kesejahteraan Masyarakat dengan Kreativitas Wirausaha dan Kelestarian Lingkungan di Desa Pantai Bahagia Area Bekasi - Prasmoro, Alloysius Vendhi; Supratman, Jasan; Spalanzani, Widya; Saputra, Daniel; Nurhidayat, Arifin; Vendhi Prasmoro, Alloysius (Jurnal Sains Teknologi dalam Pemberdayaan Masyarakat, 2025)
The issue of community welfare in rural areas is a major concern in almost all villages in general. With this problem, villages hope for solutions by collaborating with several parties. One such collaboration is the Community Service Program (KKN) implemented by the campus, namely the KKN program implemented by the Faculty of Engineering, Bhayangkara University, Jakarta Raya, which was implemented in Pantai Bahagia Village, Muara Gembong District, Bekasi Regency, West Java Province. Based on surveys and observations in Pantai Bahagia Village, with initial results, the main program in the Entrepreneurship Sector is increasing entrepreneurial creativity with good marketing strategies to increase consumer appeal. Meanwhile, the Environmental Sustainability sector has a major problem, namely coastal abrasion. The KKN work program from the results of the observation was agreed upon, namely entrepreneurship counseling with branding and packaging strategies and mangrove planting. The implementation process involves village officials, MSME entrepreneurs, village residents and the KKN team. The results of the implementation have a positive impact on the residents of Pantai Bahagia Village, namely that the villagers understand more about how to increase consumer appeal with branding and packaging strategies and the importance of planting mangroves to prevent abrasion in coastal areas in Pantai Bahagia Village, Muara Gembong District, Bekasi Regency.